Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Determine the solution set of the system of equations [tex]\(y = x^2 - 6x + 12\)[/tex] and [tex]\(y = 2x - 4\)[/tex].

[tex]\[
\begin{array}{|c|c|}
\hline
\text{Step} & \text{Equation} \\
\hline
\text{Step 1} & x^2 - 6x + 12 = 2x - 4 \\
\hline
\text{Step 2} & x^2 - 8x + 16 = 0 \\
\hline
\end{array}
\][/tex]

Which represents the solution(s) of this system of equations?

A. [tex]\((4, 4)\)[/tex]
B. [tex]\((-4, -12)\)[/tex]
C. [tex]\((4, 4)\)[/tex] and [tex]\((-4, 12)\)[/tex]
D. [tex]\((-4, 4)\)[/tex] and [tex]\((4, 12)\)[/tex]


Sagot :

To determine the solution set of the system of equations:

[tex]\[ y = x^2 - 6x + 12 \][/tex]
[tex]\[ y = 2x - 4 \][/tex]

we need to find the points [tex]\((x, y)\)[/tex] where both equations intersect. Let's follow the steps to determine the solution(s):

### Step 1: Set the equations equal to each other.

Given the equations:
[tex]\[ y = x^2 - 6x + 12 \][/tex]
[tex]\[ y = 2x - 4 \][/tex]

Setting them equal to find where they intersect:
[tex]\[ x^2 - 6x + 12 = 2x - 4 \][/tex]

This step is shown in the table as follows:
[tex]\[ x^2 - 6x + 12 = 2x - 4 \][/tex]

### Step 2: Simplify the equation.
We need to move all terms to one side of the equation to set it equal to zero:
[tex]\[ x^2 - 6x + 12 - 2x + 4 = 0 \][/tex]
Simplify the equation:
[tex]\[ x^2 - 8x + 16 = 0 \][/tex]

This simplified equation is shown in the table as:
[tex]\[ x^2 - 8x + 16 = 0 \][/tex]

### Step 3: Solve the quadratic equation.
The equation [tex]\(x^2 - 8x + 16 = 0\)[/tex] can be solved by factoring or using the quadratic formula. Here, it's straightforward to recognize that it is a perfect square:

[tex]\[ (x - 4)^2 = 0 \][/tex]

Solving for [tex]\(x\)[/tex]:
[tex]\[ x - 4 = 0 \][/tex]
[tex]\[ x = 4 \][/tex]

So, we have one solution: [tex]\(x = 4\)[/tex].

### Step 4: Find the corresponding [tex]\(y\)[/tex] value.
To find the [tex]\(y\)[/tex] value corresponding to [tex]\(x = 4\)[/tex], we can substitute [tex]\(x = 4\)[/tex] back into either original equation. Let's use the second equation [tex]\(y = 2x - 4\)[/tex]:

If [tex]\(x = 4\)[/tex]:
[tex]\[ y = 2(4) - 4 \][/tex]
[tex]\[ y = 8 - 4 \][/tex]
[tex]\[ y = 4 \][/tex]

So, the corresponding point is [tex]\((4, 4)\)[/tex].

### Final answer:
The point of intersection, and thus the solution to the system of equations, is:
[tex]\[ (4, 4) \][/tex]

Hence, the correct answer is:

[tex]\[ \boxed{(4,4)} \][/tex]